Homogeneous dielectric barrier discharge in CO2. (1st April 2023) - Bajon, C; Dap, S; Belinger, A; Guaitella, O; Hoder, T; Naudé, N
Abstract: This study investigates dielectric barrier discharges generated in CO2 at atmospheric pressure. According to the literature, under these conditions, discharges usually work in the filamentary regime. On the contrary, the experimental results reported in the present study demonstrate for the very first time that it is also possible to obtain a diffuse CO2 discharge under these conditions. The diffuse regime appears to be related to a memory effect mechanism occurring at the dielectric surface. Both the filamentary and diffuse regimes were compared in this work based on electrical measurements coupled with intensified charged coupled device (iCCD) imaging and optical emission spectroscopy. The clear difference between both regimes is discussed.